Evaluation of the Healing Properties of Pentaclethra Macrophylla Seed Pod on Diabetic Wounds - Okiemute Rosa, Johnson-Ajinwo; Jesam , Ubangha (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Pentaclethra macrophylla has gained attention in recent years for its potential as a wound healing agent. Pentaclethra macrophylla, also known as Oil Bean tree, is a plant that is native to tropical Africa and has a long history of use in traditional medicine for various ailments. However, one part of the plant has been overlooked as a waste product- the seed pod. While studies have shown that the seed has some wound healing property, little study has been carried out on the seed pod of Pentaclethra macrophylla. This study evaluated the wound healing potential of the dichloromethane-methanol extract of Pentaclethra macrophylla seed pod on diabetic wounds. The extract was evaluated for its phytochemical content which was found to contain tannins and triterpenoids. The extract of P. macrophylla was constituted into a cream and administered topically for evaluating the wound healing potential in excision wound model for fourteen days. Thermazene was used as a positive control for wound healing in excision wound model. The extract treated groups showed wound healing properties compared with the control. The 1000 mg extract showed better wound healing activity compared to the positive control group at P<0.05. The result may be attributed to the phytoconstituents such as tannins and triterpenoids present in it in higher concentrations which due to their individual or cumulative effect enhances wound healing. These findings therefore justify the inclusion of this plant in the management of wound healing.